PHRASEOLOGIZED UTTERANCES IN THE ACTUALIZATION OF PRAGMATIC COMPONENTS OF MEANING IN DIALECT DISCOURSE - Holianych, Mariia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The article characterizes the most common types of phraseologized units functioning in the speech of residents of Tyudiv village (Kosiv district, Ivano-Frankivsk region) and reveals their role in the actualization of pragmatic components of meaning in communicative interaction. In particular, it is emphasized that these linguistic units: serve as an important means of shaping the dialectal linguistic worldview; generalize typical communicative situations, facilitating the disclosure of the intentions of communicative partners; act as significant carriers of implicit meanings, the decoding of which enables speakers to construct dialogue either as cooperative, avoiding conflicts, or as confrontational. Among various types of phraseologized units widespread in Hutsul dialect discourse that contribute to the actualization of pragmatic components of meaning, special attention is given to the linguistic unit ny s’miiu pytaty (“I dare not ask”). The article demonstrates that this phraseologized unit is an important meaning-forming component of a potential question posed by the addresser, contributing to the formation of semantic components that influence the course of communication and the actualization of each communicative partner’s program of practical behavior –namely, knowledge of how to respond to the speech actions of the interlocutor in typical situations. It is emphasized that the phraseologized unit ny s’miiu pytaty functions as a specific pragmatic signal indicating the nature of the addresser’s communicative intentions – to achieve a communicative goal. Therefore, the addresser constantly keeps in focus the model of the addressee, anticipating how the latter may perceive and interpret the question.